Critical O(N) models above four dimensions: Small-N solutions and stability - Eichhorn, Astrid; Janssen, Lukas; Scherer, Michael (Arxiv, 2016)
We explore O(N) models in dimensions $4<d<6$. Specifically, we investigate models of an O(N) vector field coupled to an additional scalar field via a cubic interaction. Recent results in
Gesehen am 11.01.2018